Age, sex, and climate factors show different effects on survival of three different bat species in a woodland bat community - Antica Culina (Global Ecology and Conservation, 2017)
1. Bats are the second largest mammalian Order and important providers of ecosystem services including insect pest control, pollination and seed dispersal. Yet, the lack of basic information on their demographic rates hampers detecting changes in population trends, and thus conservation efforts. 2. The elusive life-styles, that leads to imperfect and biased detection, limits the quantity of individually based information as well as the extent to which information can be utilised to assess accurate and unbiased demographic rates. 3. We overcome the problem of imperfect and biased detection using a multilevel capture-mark-recapture framework to produce robust estimates of survival during hibernation period, and to evaluate the effect of age, sex, social group, and external weather factors on survival and capture heterogeneity in three vespertilionid species (Myotis daubentonii, M. nattereri, and Plecotus auritus) from the same woodland community. 4. While controlling for emigration and for the species-specific roosting group structure, we show that females survive better than males in two species, and that adults survive better than juveniles in all species - these survival differences being species-specific. Only one external environmental factor (average summer temperature) explained a substantial proportion of the between-year variation in M. daubentonii survival. 5. Our study provides, for the first time, a robust estimate of annual survival in bats. We advocate careful attention to possible sources of biases when studying survival rates in the wild, considering species-specific life-history and population-specific features. Considering these factors that influence wider community responses to environmental conditions is important for the effective conservation management of an area.